BACK PAIN IN PARKINSONISM: EXPLORING PAIN GENERATORS AND INTERVENTIONAL MANAGEMENT: A CASE SERIES - Hamdani, Ismi; Lie Anto; Irma Savitri; Tiara Aninditha; Nurul Fadli; Yusak Mangara Tua Siahaan; Dyah Tunjungsari; Henry Riyanto Sofyan (Fakultas Kedokteran Universitas Sriwijaya, 2026)
Pain is a common non-motor symptom in parkinsonism, often overlooked despite its significant clinical impact. The most common form is Parkinson's disease (PD), followed by secondary and atypical parkinsonisms such as PSP. Two cases presented with musculoskeletal-spinal pain as the chief complaint: a PD patient with upper back pain that improved after an erector spinae nerve block, and a PSP patient with lumbar facet pain that improved after an intra-articular steroid injection. Pain in parkinsonism can originate from muscles, bones, joints, discs, ligaments, fascia, or nerves, requiring careful evaluation. Both cases demonstrate the effectiveness of pain injection interventions in patients unresponsive to conservative therapy. Appropriate pain assessment and management are crucial to improving the quality of life of parkinsonism patients.